Mineral Mining Resource Management Company's Social And Environmental Responsibility Policy Associated With The Justice Principle - Rusli, Tami; Jainah, Zainab Ompu; B, Erlina; Karjoko, Lego; Handayani, I Gusti Ayu Ketut Rachmi (The journal of contemporary issues in business and government, 2021)
The social and environmental responsibilities of mineral mining resources management companies need supervision in the implementation to not deviate from the state's objectives. This research is about how the policy of social and environmental responsibilities of mineral mining resources management company associates with the local community's principle of justice. This research is research with the normative juridical approach by reviewing legislation relating to corporate social responsibility and the environment. The results show that the social responsibility policy in mineral mining resources management focuses on environmental development programs but does not stand out due to the absence of standards and uniform indicators. The emphasis of policy focus is more on compliance with the Environmental Protection and Management Act. Suggestions for the sake of fulfilling the principle of justice and for legal certainty, the policy of Government Regulation governing social and environmental responsibility needs to be published soon.